2008
DOI: 10.1183/09031936.00075107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to progressive massive fibrosis in coal miners

Abstract: Progressive massive fibrosis (PMF) is a chronic interstitial lung disease with a complex aetiology that can occur after cumulative dust exposure. A case-control study was conducted to test the hypothesis that single nucleotide polymorphisms (SNPs) within genes involved in inflammatory and fibrotic processes modulate the risk of PMF development.The study population consisted of 648 underground coal miners participating in the National Coal Workers Autopsy Study, of which 304 were diagnosed with PMF. SNPs that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
(29 reference statements)
1
20
0
3
Order By: Relevance
“…Of these, 562 articles were excluded based on the inclusion criteria. Finally, 14 articles involving 20 studies met the inclusion criteria and were included in the final meta-analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The data were gathered from a total of 1935 pneumoconiosis cases and 3753 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 562 articles were excluded based on the inclusion criteria. Finally, 14 articles involving 20 studies met the inclusion criteria and were included in the final meta-analysis [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . The data were gathered from a total of 1935 pneumoconiosis cases and 3753 controls.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The data were gathered from a total of 1935 pneumoconiosis cases and 3753 controls. Six of these studies investigated the association between TNF-a gene -238 G/A polymorphism and pneumoconiosis 10,12,15,17,18,22 , and 14 studies involved TNF-a gene -308 G/A polymorphism [10][11][12][13][14][15][16][17][18][19][20][21][22][23] . Table 1 shows the studies identified and their main characteristics.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…For workers exposed to asbestos, it is suggested that GSTP1*105Val allele and low EPHX1 activity genotype (glutathione S-transferases and microsomal epoxide hydrolase, respectively) are protective 5) . Yucesoy et al 6) conducted a case-control study to test the hypothesis that the polymorphisms within genes involved in inflammatory and fibrotic processes modulate the risk of progressive massive fibrosis among underground coal miners, and observed that the polygenotype of VEGF +405/ICAM-1 +241/IL-6 -174 (C-A-G) conferred an increased risk for PMF (VEGF = vascular endothelial growth factor and ICAM = epidermal growth factor intercellular cell adhesion molecule). The susceptibility, of course, must be concern in non-occupational exposures, as reported by Liao YT et al 7) that residents in Taiwan exposed to high levels of arsenic (cumulative exposure >14.7 ppm-year or drinking artesian well water >21 yr) and carrying the R-C-S haplotype (constituted by polymorphisms of paraoxonase genes PON1 Q192R, -108C/T and PON2 C311S) were associated with the incidence of electrocardiogram abnormality.…”
mentioning
confidence: 99%